2016
DOI: 10.1007/s00122-016-2820-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study reveals genetic architecture of coleoptile length in wheat

Abstract: Eight QTL for coleoptile length were identified in a genome-wide association study on a set of 893 wheat accessions, four of which are novel loci. Wheat cultivars with long coleoptiles are preferred in wheat-growing regions where deep planting is practiced. However, the wide use of gibberellic acid (GA)-insensitive dwarfing genes, Rht-B1b and Rht-D1b, makes it challenging to breed dwarf wheat cultivars with long coleoptiles. To understand the genetic basis of coleoptile length, we performed a genome-wide assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 48 publications
7
37
0
Order By: Relevance
“…Based on the threshold value of -log10 (p-value) > 3, we identified 14, 1, 1, 2, 18, 6, and 4 significant SNPs on chromosomes 2A (QCL.sdsu-2AS), 2B (QCL.sdsu-2BS), 2D (QCL.sdsu-2DS), 3B (QCL.sdsu-3BS), 4B (QCL.sdsu-4BS and QCL.sdsu-4BL), 5B (QCL.sdsu-5BL), and 6B (QCL.sdsu-6BL), respectively ( Figure 2). Like previous studies (Rebetzke et al, 2007a;Rebetzke et al, 2014;Li et al, 2017), we also found Rht-B1, a Gibberelin (GA) insensitive dwarf allele to be associated with coleoptile length. Out of 298 genotypes, 201 (67.4%) carried the dwarf allele (allele 2) and 84 (28.2%) carried the tall allele (allele 1) of Rht-B1.…”
Section: Marker Trait Associations (Mtas)supporting
confidence: 87%
See 3 more Smart Citations
“…Based on the threshold value of -log10 (p-value) > 3, we identified 14, 1, 1, 2, 18, 6, and 4 significant SNPs on chromosomes 2A (QCL.sdsu-2AS), 2B (QCL.sdsu-2BS), 2D (QCL.sdsu-2DS), 3B (QCL.sdsu-3BS), 4B (QCL.sdsu-4BS and QCL.sdsu-4BL), 5B (QCL.sdsu-5BL), and 6B (QCL.sdsu-6BL), respectively ( Figure 2). Like previous studies (Rebetzke et al, 2007a;Rebetzke et al, 2014;Li et al, 2017), we also found Rht-B1, a Gibberelin (GA) insensitive dwarf allele to be associated with coleoptile length. Out of 298 genotypes, 201 (67.4%) carried the dwarf allele (allele 2) and 84 (28.2%) carried the tall allele (allele 1) of Rht-B1.…”
Section: Marker Trait Associations (Mtas)supporting
confidence: 87%
“…Molecular markers linked to genes or quantitative trait loci (QTLs) can facilitate simultaneous marker-assisted breeding and pyramiding for several traits, avoiding laborious and timeconsuming phenotyping. Recently, a few QTL mapping studies in spring wheat have mapped several QTLs that control coleoptile length on chromosomes 1A, 1B, 1D, 2B, 2D, 3A, 3B, 3D, 4A, 4BS (Rht-B1b), 4DS (Rht-D1b), 5A, 5B, 5D, 6A, 6B, and 7B (Rebetzke et al, 2007a;Spielmeyer et al, 2007;Yu and Bai, 2010;Rebetzke et al, 2014;Singh et al, 2015;Li et al, 2017) However, linkage mapping studies have lower power in identifying QTLs with smaller effect and typically demarcate the QTLs to large genomic regions of 15-20 cM (Tuberosa et al, 2002;Korte and Farlow, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most QTL (quantitative trait locus) studies on seedling heterotrophic performance were based on traditional linkage mapping using bi‐parental populations either in crop species (Bettey et al 2000, Lee et al 2001, Limami et al 2002, Finch‐Savage et al 2010, Rebetzke et al 2014), or in our previous studies in M. truncatula (Dias et al 2011, Vandecasteele et al 2011, Youssef et al 2016). Few were based on GWAS analyses (Li et al 2016, in wheat). Despite the potential of plant natural diversity, it is an underused resource for physiological and genetic (QTL) studies regarding seedling establishment.…”
Section: Introductionmentioning
confidence: 99%